2019
DOI: 10.1097/fch.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Model of HPV Vaccine Series Completion in Adolescent Hispanic Males

Abstract: HPV vaccine series completion among adolescent Hispanic males (35%) is lower than the Healthy People 2020 80% goal. This directed qualitative content analysis identified mother's beliefs about their sons completing the series. We found that mothers (N=19): 1. Express positive feelings; 2. Believe the vaccine has positive effects; 3. Identify the father, and doctor as supporters and friends as non-supporters; 4. List health insurance, transportation and clinic reminders as facilitators and 5. Mention affordabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
(36 reference statements)
3
20
0
Order By: Relevance
“…These finding support the results of previous studies conducted with other racial and ethnic minority groups [23,31,[38][39][40][41][42] and Latinos [15][16][17][18]20,[23][24][25][26] documenting the unique and crucial influence of healthcare providers on fathers' acceptability and willingness to vaccinate their children against HPV. Although the vast majority of fathers participating in our study reported that their child's mother was the primary parent taking children to healthcare visits, fathers also mentioned close communication with their wives and/or partners about their children's health visits.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These finding support the results of previous studies conducted with other racial and ethnic minority groups [23,31,[38][39][40][41][42] and Latinos [15][16][17][18]20,[23][24][25][26] documenting the unique and crucial influence of healthcare providers on fathers' acceptability and willingness to vaccinate their children against HPV. Although the vast majority of fathers participating in our study reported that their child's mother was the primary parent taking children to healthcare visits, fathers also mentioned close communication with their wives and/or partners about their children's health visits.…”
Section: Discussionsupporting
confidence: 90%
“…They used a semistructured interview guide to ensure that similar topics were discussed with all participants [28]. The interview guide included open-ended questions based on available literature and was designed to elicit participants' perceptions and understanding of HPV infection, HPV-associated cancers, and the HPV vaccine [20,[29][30][31]. In addition, interviewers asked follow-up questions and used targeted probes to clarify information and/or collect additional relevant information based on information shared by each participant.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents in Brazil seem to be in favor with an acceptance of 86% [ 25 ], whereas parts of the USA (43%) and France (38%) present much lower figures [ 14 , 15 ]. Mothers are in favor of vaccinating their sons [ 27 ] but there may be a discrepancy between their stated belief that vaccination is important and their actual intention to have their sons vaccinated [ 28 ]. Their intention may not always mean that the child in the end becomes vaccinated [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further reasons not to vaccinate the sons were the belief that the vaccine is harmful and/or gives limited benefit [ 42 ], fear of unknown side-effects [ 17 , 33 , 40 ] and vaccine hesitancy in general [ 15 , 42 ]. Cost is also a significant barrier, especially for economically underprivileged parents [ 27 , 43 ].…”
Section: Resultsmentioning
confidence: 99%